The influence of differently functionalized nanodiamonds on proliferation, apoptosis and EMT/MET phenomena in 2D and 3D tumor cell cultures. Issue 45 (4th November 2021) - Shirley, Anup James; Schweeberg, Sarah; Waag, Thilo; Peindl, Matthias; Dandekar, Gudrun; Walles, Heike; Jakob, Franz; Krueger, Anke; Ebert, Regina
Abstract : Three different nanodiamonds (ND-BA, NDprist, ND-BQ) were applied in 2D and 3D models to LNCaP prostate and MDA-MB-231 and MCF-7 breast cancer cells. Proliferation, apoptosis and expression of EMT/MET markers were analyzed by qPCR and Western Blot. Abstract : Nanodiamonds (ND) have been suggested to have several potential uses in biomedicine, since they are seemingly biocompatible. However, data about the biological effects of ND in physiological conditions are scarce. In this study, we observed that prostate cancer cells (LNCaP) and breast cancer cells (MDA-MB-231 and MCF-7) cultured with ND show morphological changes and altered gene and protein expression. In 2D we could detect only slight effects of ND on cell growth and apoptosis induction. Therefore, we applied different functionalized ND in a novel 3D cell culture model that reflects better tissue conditions compared to conventional 2D cell cultures. In 3D proliferation was reduced by all nanoparticles and benzoquinone functionalized ND induced cell death. As the used decellularized scaffold maintains the tissue architecture, we could also functionally investigate if nanoparticles induce cell migration into deeper layers and if they display markers of Mesenchymal Epithelial Transition (MET). We detected in more mesenchymal and invasive growing MDA-MB-231 cells less vimentin and increased levels of pan-cytokeratin expression after ND treatment, which indicates a MET induction. Our observations suggest that the presence of ND stimulates MET, with varying degrees of transition. The observation that ND do not support the opposite, EMT, is beneficial, since EMT is known to play a major role in tumor metastasis. However, a special focus should be placed on the characterization of biological effects to be able to guarantee the safety of ND in clinical use.